Predictors of burnout among supply chain management professionals. (22nd February 2023) - Atkins, Ryan; Sener, Abdurrezzak; Drake, Matthew J.; Marley, Kathryn
The competitive market for supply chain management (SCM) talent has increased the importance of retaining SCM employees. Despite generally positive opinions of SCM careers, high levels of turnover among SCM professionals exist, and burnout has often been cited as a cause for turnover. Based on a survey of 104 US-based SCM professionals, and using person-environment fit as a theoretical background, this study found that burnout is increased when workers perceive a deficit in the amount of remote work permitted and when working overtime and non-traditional hours (OT/NT), whereas burnout is reduced by pay satisfaction and a perception of transformational leadership. There is also an interaction between pay satisfaction and OT/NT, with OT/NT taking precedence over pay satisfaction in driving feelings of burnout. Very few studies have addressed talent management among SCM professionals, and this study has identified insights that are relevant to managers and to future research on this subject.